2017
DOI: 10.1093/ckj/sfx135
|View full text |Cite
|
Sign up to set email alerts
|

Medication discrepancies in late-stage chronic kidney disease

Abstract: BackgroundLate-stage chronic kidney disease (LS-CKD) can be defined by glomerular filtration rate (GFR) 0–30 mL/min. It is a period of risk for medication discrepancies because of frequent hospitalizations, fragmented medical care, inadequate communication and polypharmacy. In this study, we sought to characterize medication discrepancies in LS-CKD.MethodsWe analyzed all patients enrolled in Northwell Health’s Healthy Transitions in LS-CKD program. All patients had estimated GFR 0–30 mL/min, not on dialysis. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Medication discrepancies are a reflection of a number of different factors that complicate medication management in chronically ill patients. In a previous study, 4 we found a diagnosis of heart failure, white race, hypertension, and the number of medications to be associated with increased number of discrepancies.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Medication discrepancies are a reflection of a number of different factors that complicate medication management in chronically ill patients. In a previous study, 4 we found a diagnosis of heart failure, white race, hypertension, and the number of medications to be associated with increased number of discrepancies.…”
Section: Discussionmentioning
confidence: 69%
“…1 We have previously reported that medication discrepancies are particularly common in patients with advanced chronic kidney disease (CKD; estimated glomerular filtration rate 0 to 30 ml/min per 1.73 m 2 ) not yet on dialysis, with 55% of patients having at least 1 discrepancy. 4 It is likely that mismatches between patients' medication use and the physician's record are more of a problem in chronic diseases. These patients are often treated with a large number of drugs 5 and are cared for by multiple physicians.…”
mentioning
confidence: 99%
“…Frequent adjustments to medications for patients with multiple medications can lead to various problems, including poor adherence, adverse effects and concerns about the new treatment [ 10 ]. These problems might be augmented in CKD patients with increased complexity to their medication regimens requiring patients to adapt to new routines, leading to other practical difficulties associated with medication changes [ 11 ]. Furthermore, the addition of medications increases the likelihood of receiving inappropriate medication, given the higher chance of drug-drug interactions among CKD patients who have an existing complex medication profile and altered pharmacokinetic profile [ 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of medications increases the likelihood of receiving inappropriate medication, given the higher chance of drug-drug interactions among CKD patients who have an existing complex medication profile and altered pharmacokinetic profile [ 5 , 12 ]. Frequent medication adjustments might also lead to harm if changes are not adhered to, such as unanticipated adverse events or drug interactions resulting from persistent use of medications that have been discontinued by the prescriber, or failure to achieve efficacy when the medicines were not adjusted as instructed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, SGLT2 inhibitors may allow deprescription of drugs [ 24 ]. This is especially interesting in diabetic patients with CKD who frequently receive multiple medications, thus compromising compliance with antidiabetic drugs and increasing the risk of medication discrepancies resulting in physicians not knowing which drugs patients are actually taking [ 26 , 27 ].…”
mentioning
confidence: 99%